Very late complications of oncotherapy in glioblastoma patients: A case series - Kalita, Ondrej; Hrabalek, Lumir; Halaj, Matej; Hok, Pavel; Franc, David; Klementova, Yvona; Dolezel, Martin; Cechakova, Eva; Sporikova, Zuzana; Drabek, Jiri; Hajduch, Marian; Tuckova, Lucie (Biomedical papers, 2022)
Background. Stroke-like syndrome is defined as a rare, delayed complication of brain oncotherapy. Cases with more favorable brain cancer diagnoses and longer life expectancy have been previously reported, but here we present, for the first time, three long-term survivors of glioblastoma with stroke-like syndromes. Methods and Results. Three young or middle-aged patients underwent tumor resection and chemoradiotherapy. They received regular clinical and imaging follow-up with stable neurological status and no signs of tumor recurrence. They exhibited varied signs and symptoms (motor and sensory deficits, aphasia, memory and cognitive disorders, seizures, and headache) accompanied by imaging abnormalities. Stroke-like syndromes developed within 2-5 days and resolved in 2-6 weeks. Diffusion-weighted MRI and T2 brain perfusion abnormalities were demonstrated in all patients. In addition, there was focal T1 MRI contrast enhancement due to blood-brain barrier disruption. In addition to tumor recurrence, classic stroke, encephalitis, metabolic and mitochondrial disorders, and post-seizure swelling should be excluded. The imaging indicated intensive MRI scanning and symptomatic medication (steroids supplemented by antiepileptics, vasoactive agents, etc.) for judicious management. With respect to the course, an invasive procedure was still considered an option. Conclusion. All stroke-like syndromes are diagnoses of exclusion. To avoid misinterpretation of imaging findings as glioblastoma recurrence and avert recall oncotherapy or redundant interventions, better understanding of delayed complications of brain tumor therapy is crucial.
Keywords: stroke-like syndrome; glioblastoma; oncotherapy; corticosteroid